Tinjauan Literatur: Akuntansi Manajemen dalam Mendukung Tata Kelola Perusahaan yang Efektif - Cailah Nasywa Afrila; Diana Indah Sri Lestari P. A; Cholis Hidayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article explores the strategic role of management accounting in supporting the implementation of effective corporate governance. In today’s complex and dynamic business environment, management accounting functions not only as an internal financial recording tool but also as a provider of relevant information for decision-making, control, and strategic planning. Using a literature review approach, this study identifies the contributions of management accounting in enhancing investment efficiency, promoting transparency through responsibility accounting, strengthening internal audit functions, and reducing information asymmetry. The integration between management accounting systems and Good Corporate Governance (GCG) principles has been proven to create synergy in both operational management and strategic oversight. The findings indicate that a well-structured, transparent, and governance-oriented management accounting system serves as a fundamental pillar for building accountable and sustainable organizations.